THE IMPACT OF THE SARS-CORONA PANDEMIC 2 ON HUMAN RIGHTS - Filipovski, Zoran; Sotiroska Ivanoska, Kalina; Galetin, Milena (International Scientific Journal Vision, 2021)
In addition to the negative aspects of the quality of life caused by the crisis from the KOVID-19 epidemic, it is in a way a foundation for the essentiality of ensuring the further development of social rights, especially in terms of health care rights. This crisis only highlights the shortcomings in the development of the corpus of these rights, of which the governments in many countries were aware, but still did not do much to improve this situation, which is negatively reflected in dealing with this health crisis, and thus in the protection of the corpus of the fundamental rights and freedoms of the citizens through the loss of their lives, as a consequence of the non-functioning of the health system.